The complete reiki handbook : basic introduction and methods of nature application : a complete guide for reiki practice - Lubeck, Walter (Delhi : Motilal Banarsidass Publishers Pvt Ltd, 1998)
This book describes the secrets and possible uses of this subtle healing force.
Keywords: Reiki (Healing system).; Mental healing; Alternative medicine